Early cardiac unloading with ImpellaCP™ in acute myocardial infarction with ventricular septal defect. (11th February 2020) - Via, Gabriele; Buson, Stefania; Tavazzi, Guido; Halasz, Geza; Quagliana, Angelo; Moccetti, Marco; Demertzis, Stefanos; Cassina, Tiziano
Abstract: Despite a relative contraindication, mechanical support with Impella™ left ventricular assist device has already been described for ischaemic ventricular septal defect treatment, either as a bridge to surgery, as intraoperative mechanical haemodynamic support, or to ensure intraprocedural haemodynamic stability during device closure. We describe two cases of ventricular septal defect complicating acute myocardial infarction, where the percutaneous ImpellaCP was implanted early (differently than previously described) with the aim of preventing haemodynamic instability, while deferring surgical repair. We present a report of haemodynamic, echocardiographic, biochemical, and clinical data of two consecutive cases of ImpellaCP use, within a minimally invasive monitoring and therapeutic approach. In two cases of subacute myocardial infarction‐related ventricular septal defect not amenable to percutaneous device closure, the use ImpellaCP was successful: it was followed by effective and rapid right and left ventricular unloading, by major haemodynamic instability prevention and protection from systemic venous congestion, from kidney and splanchnic organ failures. This allowed bridging to appropriately timed surgical repair. These cases suggest a potentially effective, clinically grounded strategy in the early management of ischaemic ventricular septal defect patients, with the aim of deferring surgery beyond the safer 7 days cutoff associated with a lower perioperative mortality.